Ecological valuation of city parks (Case study for Mataram City) - Suripto Suripto; Jupri, A.; Farista, B.; Virgota, A.; H. Ahyadi (Jurnal Biologi Tropis, 2021)
City parks, apart from having an aesthetic function as a place for recreation, also have an ecological function with vegetation components to soften the microclimate. Vegetation analysis was carried out in six city parks in Mataram City to determine the vegetation structure. Microclimate factors of the park, namely light intensity, air temperature and humidity inside and outside the park during the day and observations of sound attenuation at night have been carried out. Climatic data is carried out to determine the park's ability to reduce heat and air temperature, increase air humidity and reduce noise and determine the park's environmental discomfort index. Of the six urban parks observed in the city of Mataram, namely the parks of Ampenan, Malomba, Udayana, Sangkareang, Mayura, and Selagalas, it is known that there are three groups of vegetation structures, namely trees-shrubs, shrubs-trees, and shrubs. Vegetation with various compositions of life forms in each city park only controls 40 to 60% of the land area of the park. Urban parks in Mataram City have a low level of ability to soften the microclimate, which is below 5%. In reducing heat and air temperature, and increasing air humidity. City parks are also known to have a low ability to reduce noise. The city parks of Ampenan, Udayana and Sangkareang have an environmental comfort level equivalent to the discomfort felt by more than 50% of the population, while the Malomba, Mayura, and Selagalas parks have a level of comfort equivalent to the discomfort felt by less than 50% of the population. The existence of urban park vegetation is only able to reduce the discomfort index of 7 to 9%.